Mental health : policies, laws and attitudes : a conversation with Elyn Saks - Burton, Howard (Ideas Roadshow Conversations Ser., 2021)
This book is based on an in-depth filmed conversation between Howard Burton and Elyn Saks, Orrin B. Evans Distinguished Professor of Law, and Professor of Law, Psychology and Psychiatry and the Behavioral Sciences at USC. During this wide-ranging conversation Elyn Saks candidly shares her personal experiences with schizophrenia and discusses the intersection of law, mental health and ethics: the legal and ethical implications surrounding mental health. Further topics include psychotropic medication and the law, criminalization and mental illness, and an exploration of which countries are more progressive with respect to important mental health policies, laws and procedures.This carefully-edited book includes an introduction, To Shorten the Odds, and questions for discussion at the end of each chapter. Howard Burton was the Founding Director of Canada's Perimeter Institute for Theoretical Physics. He holds a PhD in theoretical physics and an MA in philosophy. This book is part of an expanding series of 100+ Ideas Roadshow conversations, each one presenting a wealth of candid insights from a leading expert in a focused yet informal setting to provide a uniquely accessible window into frontline research and scholarship that wouldn't otherwise be encountered through standard lectures and textbooks.